Perbedaan Metode Pembelajaran Kooperatif Tipe Jigsaw dan Konvensional terhadap Prestasi Belajar Mahasiswa - Suwarno Suwarno (JIATAX (Journal of Islamic Accounting and Tax), 2018)
One of the factors that affect student achievement is a learning model. Conventional learning models provide a low success rate compared with the cooperative model. Conventional learning model gives a major role to the faculty and students tend to be passive. While the cooperative learning model provides the opportunity for students to learn actively and teachers act as facilitators. One model is a model of cooperative learning jigsaw. Jigsaw model study is a model of learning in groups in which each individual is required to play an active role in contributing to the group. The sample was accounting students who take the course of financial accounting. Results of testing using t test showed that there are significant differences between conventional teaching with the type of jigsaw. The average student results showed that the average achievement of student learning is better than the conventional type of cooperative learning jigsaw.Keywords : Achievement, conventional learning, Jigsaw